Advancements in greenhouse gas emission reduction methodology for fluorinated compounds and N2O in the semiconductor industry via abatement systems - Zhou, Yue; Li, Yuanzhe; Ong, Emily (Frontiers in Energy Research, 2024)
Greenhouse gases (GHGs), particularly fluorinated compounds (FCs), nitrous oxide (N2O), and nitrogen trifluoride (NF3), contribute significantly to climate change, and the semiconductor industry is a notable emitter of these gases. This report introduces an innovative methodology for GHG emission reduction in the semiconductor industry by utilizing advanced abatement systems, referencing Clean Development Mechanism (CDM) published methods AM0078 and AM0111. The proposed methodology shows promising potential, with substantial reductions in FCs, N2O, and NF3 emissions, positioning the semiconductor industry as a key player in climate change mitigation efforts. The main results indicate that by applying the latest abatement systems, a significant reduction in the targeted GHGs can be achieved. The methodology’s verification process confirms the effectiveness of GHG reduction, ensuring that semiconductor manufacturing's environmental impact is minimized. Our findings suggest that the implementation of this methodology could lead to industry-wide adoption, resulting in a substantial contribution towards stabilizing atmospheric GHG concentrations.